PENGARUH KARAKTERISTIK ANGGARAN TERHADAP KINERJA MANAJERIAL (Studi Empiris Pada Dinas Koperasi Di Kabupaten Jember) - Ibna Kamilia (Jurnal Ilmiah Akuntansi Indonesia, 2016)
Budget is used as target of achievement for various programs that are arranged whether in short term planning process and in long term. Besides that, budget is needed to keep a company survive in dynamic business circumstance and also to improve responsibility in finance and to ease the company's achievements. Characters in budget arrangement dimension have to fulfill several aspects in attitude, such as: budget participation, budget difficulties level, top management involvement, justice principal, and organization structure. Aim of this research is to analyze budget characters whether in partial or on managerial performance simultaneously. This research uses primary data that are collected by doing questioners to the respondents. Population of this research is the whole employees of Cooperation Service of Jember Region that are involved in budget arrangement process. However, amount of the whole samples that is used in this research are 40 respondents.Keywords: Budget Characteristic, Managerial Performance